Hi, I need help with these. Simplfy as much as possible. ((3x2^n+1) + (5x2^n)) / ((7x2^n) - (3x2^n-1)) solve for x 2y-1/1-x = 2y+1 x not =1 , y not =-1/2 solve for s 2s - 2/s = 3 s not = 0
Follow Math Help Forum on Facebook and Google+
Originally Posted by tim_mannire Hi, I need help with these. Simplfy as much as possible. ((3x 2^n+1) + (5x2^n)) / ((7x2^n) - (3x2^n-1)) solve for x 2y-1/1-x = 2y+1 x not =1 , y not =-1/2 solve for s 2s - 2/s = 3 s not = 0 ((3x should be on the same line as the rest of it.
View Tag Cloud